Multiple environmental changes induce interactive effects on bacterial degradation activity in the Arctic Ocean - Piontek, Judith; Sperling, Martin; Nöthig, Eva-Maria; Engel, Anja (Limnology and oceanography, 2015)
The Arctic Ocean faces multiple environmental changes induced by climate change on both global and regional scale. In addition to global changes in seawater temperature and pH, Arctic waters receive organic matter enrichment due to increasing pelagic primary production, enhanced sea ice melting and increasing terrestrial carbon loads. We experimentally tested individual and combined effects of warming, acidification and organic matter amendment on growth, biomass production and extracellular enzyme activities of bacterioplankton in Fram Strait during early summer. Results reveal pH optima of 6.7–7.6 for extracellular leucineaminopeptidase and below pH 6.0 for beta-glucosidase in the West Spitsbergen Current. These optima well below the current seawater pH imply increasing hydrolytic activity with ongoing ocean acidification. However, the new synthesis of extracellular enzymes during 4-d incubations obscured the biochemical pH effects. Elevated temperature and carbohydrate supply had strongly interactive effects on bacterial biomass production in both Atlantic Water of the West Spitsbergen Current and Polar Water of the East Greenland Current. Activation energies ranged from 45 kJ mol−1 to 52 kJ mol−1 at in situ substrate concentration, while substantially higher values of 122–174 kJ mol−1 could be estimated from incubations with carbohydrate addition. The net loss of total amino acids in carbohydrate-amended incubations was significantly reduced at elevated temperature in all experiments, suggesting enhanced de novo synthesis. Our findings show that the complexity of combined effects must be considered to better assess the potential of climate change to alter biogenic carbon and energy fluxes in marine systems.